Fostering Patriotism Through Unity: Implementation of Pancasila's Third Principle in Elementary Character Education - Yuliana, Nana Pirda; Idris, Muhamad; Irawan, David Budi (Papanda Publisher, 2025)
In Indonesia's diverse society, implementing Pancasila's third principle—